Produção enxuta e teoria das restrições : proposta de um método para implantação conjunta na indústria de bens de capital sob encomenda - Votto, Rodrigo Goulart (2012)
Over the years, the task of developing and managing production systems has become increasingly complex and, currently, to face the changing customer demands and global competition, managers have the difficult task of combining the efficiency of mass production with customization of pre-industrial craft production era. In this context, the Engineering to Order Capital Goods Industry, exposed to a very adverse market conditions such as high cyclical instability of demand for its products, which depends exclusively on the economy expansion moments, causing, therefore, longer cycles of fluctuation demand with long periods of stagnation followed by periods of high demand, have sought for modern production management strategies, already consolidated in more dynamic segments of the economy, such as lean production and the theory of constraints, to improve production flow and minimize the impact inherent in these production systems with high variety and low volume production, high levels of work-in-process, functional production layouts, high varied workloads, excess of materials handling, etc. This paper studies the Engineering to Order Capital Goods Industry, especially large capital goods, also known as Large Assemblies production systems, aiming to propose a method of joint implementation of lean principles and theory of constraints to simplify the material and information flow, propose the use of suitable SCO (ordering systems) and reduce production lead time in this environment.